PENERAPAN TERAPI RELAKSASI NAFAS DALAM UNTUK MENGURANGI SKALA NYERI DADA PADA PASIEN CONGESTIVE HEART FAILURE (CHF) YANG SEDANG DI RAWAT DI RSUD BAYU ASIH PURWAKARTA - Serly, Serly; Grace Evelyn; Suryati, Suryati (Bajang Institute, 2023)
Congestive Heart Fallure (CHF) or congestive heart failure is a condition in which the heart fails to pump blood to meet the needs of the body's cells for adequate nutrients and oxygen. According to data from the World Health Organization (WHO, 2016) that as many as 17.9 million people in the world died from cardiovascular disease or the equivalent of 31% of 56.5 million global deaths and more than ¾ or 85% of deaths caused by cardiovascular disease. often occurs in developing countries. The problem that will arise in patients is Congestive Heart Fallure (CHF) pain in the chest. To overcome the intensity of pain can be done the application of deep breathing relaxation techniques. This scientific paper aims to provide an application of deep breathing relaxation therapy to reduce pain scale in patients with congestive heart failure (CHF) who are being treated at Bayu Asih Hospital, Purwakarta. From the intervention carried out for 3 meetings with the results of the intensity of the severe pain scale (6) on the first day